Analysis of the Technology Acceptance Model (TAM) for SIMKREASI Users at USN Kolaka - Muh. Nurtanzis Sutoyo; Anjar Pradipta (PT FORMOSA CENDEKIA GLOBAL, 2023)
An organization is tested for its ability to compete and strategies that can take advantage of all existing strengths and opportunities. This can be done if the organization is able to make decisions in the use of well-designed information systems. Based on the results of research and discussion, it can be seen that the quality of information affects application usage satisfaction with a T-statistic value of 7,827, the quality of information also affects the intensity of application use with a T-statistic value of 2,941, usability quality affects application usage satisfaction with a T-value statistic of 6,026, the quality of usability affects the intensity of application use with the acquisition of a T-statistic value of 3,080, the quality of interaction affects the satisfaction of using the application with a T-statistic value obtained of 2,362, the quality of interaction influences the intensity of application use as indicated by the value of the T-statistic of 3,129, and satisfaction affects the intensity of application use with the acquisition of a T-statistic of 3,792